The politics of identity in Visigothic Spain - Wood, Jamie P., 1978-
1 online resource (xii, 275 pages)
Keywords: Previous scholarship has interpreted Bishop Isidore of Seville (d. 636) retrospectively as the architect of the medieval Spanish church, as the father of Spanish identity, and as a key figure in the transmission of Classical and Patristic learning to the Middle Ages. Drawing on recent studies on identity formation in the early medieval period and an upsurge in interest in late antique Spain, this book examines the historical Isidore as a social actor managing a complex web of responsibilities and relationships. A comparative analysis of Isidore's historical works demonstrates that writing about the past was a method for reconciling Visigothic kings, nobles and Spanish bishops in a period of transformation. This results in a fresh portrait of Isidore as motivated, both politically and pastorally, to balance competing interests and ensure the spiritual and material security of the people of Spain.